School Counseling Skills Needed To Activate Distance Learning In Light Of Covid-19 Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem and the aim of the study: COVID-19 pandemic had affected all sectors including the educational sector. The educational system shifted from the traditional face to face teaching method to use online means in order to ensure the safety of the students and the social distancing. These changes also affected the roles of the educational members including the school counselors.   Therefore, the study aims to investigate the school counseling skills needed in light of COVID-19.Research Method: The study relied on the descriptive approach and administrated by a questionnaire to collect the data from the school counselors. The study sample consisted of (400) Jordanian schools counselors from both genders whom chosen randomly to respond to the study tool.Results: The study found that the main required skills are the cognitive, emotional and humanitarian skills, professional and ethical skills, technical and electronic skills.  The study found that the most needed counseling skills are similar to the traditional education, but due to the shift from the from face to face education to the distance education the most concentration will be on the counselors IT skills.